A Game Changing, One of Its Kind Flap: The Boomerang-Shaped Extended Rectus Abdominis Myocutaneous Flap with Latissimus Dorsi Myocutaneous Flap - Vasudevan, Srikanth; N., Ananteshwar Y.; Shetty, Mayur; Marwah, Annika; Shetty, Pooja; B., Serena; Yande, Aashita; Tewari, Chinmay (Indian Journal of Plastic Surgery, 2025)
Reconstruction of extensive limb defects is particularly difficult when standard flaps like the anterolateral thigh flap, latissimus dorsi (LD) flap, or the less popular large flap, boomerang-shaped extended rectus abdominis (BERAM) flap, are insufficient to cover the extensiveness of the raw area, even after extending with vein grafts. The BERAM and LD myocutaneous flap combines two flap areas into a single tissue unit, offering a novel solution to the issue. Interposition vein grafts help extending the reach further and avoids the anastomosis in a probable zone of injury area. In our experience, it gives the largest possible tissue for coverage compared to any two separate free flaps especially in children with a good caliber, reliable pedicle.
Keywords: soft tissue reconstruction of extremities; longest free flap; boomerang-shaped extended rectus abdominis myocutaneous flap